Plant-Rich Dietary Patterns, Plant Foods and Nutrients, and Telomere Length - Crous-Bou, Marta (Adv Nutr, 2019)
The world's population is aging as a consequence of an increased global life expectancy. Identifying simple strategies to promote healthy aging (i.e., absence of major chronic diseases, preserved physical and cognitive functions, intact mental health, and good quality of life) have emerged as a major public health concern. Identifying biomarkers to better characterize the aging process is a research priority. Telomeres are repetitive DNA sequences at chromosome ends that prevent the loss of genomic DNA, protecting its physical integrity. Telomere length (TL) is considered a biomarker of aging: shorter telomeres are associated with a decreased life expectancy and increased rates of age-related chronic diseases. Telomere attrition has been shown to be accelerated by oxidative stress and inflammation. Since edible plants contain plenty of compounds with antioxidant and anti-inflammatory properties, it is plausible that their sustained consumption might help counteract telomere attrition. In this narrative review, we update evidence on the association between plant-rich dietary patterns and plant-based foods and TL. First, we summarize findings from observational studies on the association between TL and 1) adherence to plant-rich dietary patterns (mainly, but not only, focused on the Mediterranean diet); 2) consumption of seeds (mostly focused on nuts, grains, and coffee); and 3) intake of carotenoids, one of the plant-derived bioactives most studied in health and disease. Second, we summarize the main randomized controlled trials evaluating the effect on TL of dietary interventions involving either plant-rich dietary patterns or plant foods. Even though evidence from trials is very limited, several observational studies have reinforced the suggestive benefits of adherence to the Mediterranean diet (a plant-rich dietary pattern), consumption of seeds (and its derivatives), and dietary intake of carotenoids on TL, which further supports the research benefits of plant-rich dietary patterns and plant foods to promote health and longevity.